The trust [videorecording (DVD)] - Cage, Nicolas, 1965-; Wood, Elijah, 1981-; Ferreira, Sky, 1992-; Lewis, Jerry, 1926-2017 (Lionsgate, 2016)
Waters and Stone are two nobody police officers working dull administrative jobs and making extra money selling stolen Civil Service Exams to other officers. When Stone hears a story about a heroin dealer quickly beating his extremely high bail, the two friends set into motion a plan to find the origin of such a large amount of cash. Through diligent police work they follow a trail that leads directly to a custom bank-style vault.